Engineered cytochrome fused extracellular matrix enabled efficient extracellular electron transfer and improved performance of microbial fuel cell - Chen, Yuan-Yuan; Yang, Fu-Qiao; Xu, Nuo; Wang, Xing-Qiang; Xie, Peng-Cheng; Wang, Yan-Zhai; Fang, Zhen; Yong, Yang-Chun (The Science of the total environment, 2022)
Microbial fuel cell (MFC) was a promising technology for energy harvesting from wastewater. However, inefficient bacterial extracellular electron transfer (EET) limited the performance as well as the applications of MFC. Here, a new strategy to reinforce the EET by engineering synthetic extracellular matrix (ECM) with cytochrome fused curli was developed. By genetically fusing a minimal cytochrome domain (MCD) with the curli protein CsgA and heterogeneously expressing in model exoelectrogen of Shewanella oneidensis MR-1, the cytochrome fused electroactive curli network was successfully constructed and assembled. Interestingly, the strain with the MCD fused synthetic ECM delivered about 2.4 times and 2.0 times higher voltage and power density output than these of wild type MR-1 in MFC. More impressively, electrochemical analysis suggested that this synthetic ECM not only introduced cytochrome of MCD, but also attracted more self-secreted electrochemically active substances, which might facilitate the EET and improve the MFC performance. This work demonstrated the possibility to manipulation the EET with ECM engineering, which opened up new path for exoelectrogen design and engineering. [Display omitted] •Curli fibers production of S. oneidensis was rescued by CsgA expression.•Synthetic cytochrome was fused to the CsgA and expressed in S. oneidensis.•The engineered curli fibers established efficient EET pathways.•The MFC performance was improved and the mechanism was proposed.